The Relationship between Personality of Single and Double Athletes of Badminton Toward Achievement Level in PB. Djarum (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2018)
Sport psychology especially regarding athlete mental processes becomes an increasingly decive contributor in the coaching and improvement of athlete achievement. An athlete should be viewed individually since the personality of each athlete is different. This research used quantitative non-Experimental method. The data analysis technique used MANOVA, at the signifiant level (α) 0,05. The population was 214 badminton athletes and the samples was 35 athletes upper 17 years old, it was used purposive sampling technique based on characteristics (goal setted by the researcher). The instrument of the research used questionnaire from SPQ 20 (Sport Personality Quesitonnaire). The result of Manova analysis showed that there was a relationship between personality of single and double athletes toward their achievement on personality aspects: achievement, conscientiousness, visualization, self-efficacy, self-talk, self-awareness, and ethics. There was a difference personality between single and double athletes, the value of seven personality aspects has sig value, 0,05. The conclusion of the research was there was a reationship between personality of single and double athletes of badminton in PB.Djarum. The researcher’s suggestion is the result of the relationship personality between single and double athletes toward their achievement in PB.Djarum is expected to be continued by other researchers and sportmen with different problem so it can obtain better research result.